Variations of Drill Methods to Improve Long Service Technique for Badminton - Sinthadila Herta Finishia; Adi S (Halaman Olahraga Nusantara : Jurnal Ilmu Keolahragaan, 2025)
Badminton is known to be a sport that heavily uses the wrist, therefore badminton has basic techniques, the first being the serve, which is the initial stroke or the stroke to start the match, followed by the smash, dropshot, netting, and lob. This study uses a quantitative approach with a pre-test and post-test design (Kharisma & Indarto, 2023). This study involved 10 badminton players from PB Surya Gemilang Salatiga. The descriptive statistical results of the pretest and posttest for long badminton serves show a minimum score of 12 and a maximum score of 21. Having a standard deviation of 2.79682 and a mean of 15.6000. Then the minimum posttest score is 28 and the maximum is 40, with a mean of 32.7000 and a standard deviation of 4.19126. The data on the long service results of badminton athletes were tested for normality with an L calculated score of 635 with n 10, and the L table significant α 0.05 which is greater than the L calculated score. The posttest results for the long serve obtained an L calculated score of 142 with n 10, and the significant L table α 0.05 was greater than the L calculated. Thus, it is concluded that the pretest results of the long serve are normally distributed. Based on the homogeneity test, a significance value of 0.501 was obtained. It can be concluded that the data is homogeneous. There is a significant influence between the average score before the treatment and the average score after the treatment, as shown by the paired sample t-test table, where the significance value of 0.01 is less than the significance level (α) of 0.05. Thus, it can be concluded that the drill method can influence the long serve results of badminton athletes from PB Surya Gemilang Salatiga.Variations in drill methods improve the long serve technique of badminton athletes.